1993
DOI: 10.1002/lary.1993.103.s58.1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the Neonatal Ear: Otoscopic Observations, Histologic Observations, and a Model for Contamination of the Middle Ear by Cellular Contents of Amniotic Fluid

Abstract: It is unknown whether childhood ear disease could be present long before symptoms provoke an initial otoscopic examination. A newborn middle ear might or might not start in a pristine, privileged state. The clinician evaluating later infant and childhood ear disease is often unaware of the status of a patient's ear from the neonatal period, the earliest time at which the tympanic membrane can be evaluated. Adding to the physician's handicap, normative otoscopic and histologic data on the neonatal ear are incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 81 publications
2
45
0
6
Order By: Relevance
“…Podemos atribuir o elevado número de Falha na primeira etapa, na EOAPD a dois fatores: o grupos de RN prematuros, que fazem parte do GBI, são mais vulneráveis a afecções de orelha média, retardo na maturação coclear e na mielinização das vias auditivas 10,18,20,21,22,23 . Mesmo tomando-se o cuidado de não realizar a avaliação audiológica antes da 37ª semana de idade corrigida, não podemos deixar de considerar essa possibilidade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Podemos atribuir o elevado número de Falha na primeira etapa, na EOAPD a dois fatores: o grupos de RN prematuros, que fazem parte do GBI, são mais vulneráveis a afecções de orelha média, retardo na maturação coclear e na mielinização das vias auditivas 10,18,20,21,22,23 . Mesmo tomando-se o cuidado de não realizar a avaliação audiológica antes da 37ª semana de idade corrigida, não podemos deixar de considerar essa possibilidade.…”
Section: Discussionunclassified
“…Mesmo tomando-se o cuidado de não realizar a avaliação audiológica antes da 37ª semana de idade corrigida, não podemos deixar de considerar essa possibilidade. O segundo fator é a presença de vérnix, resíduos, descamação epitelial no MAE, alterações nas membranas timpânicas, alterações de orelha média, não absorção do líquido amniótico, oclusão parcial ou total do MAE por pequenas porções de resíduos até aproximadamente o sétimo dia de vida do RN 10,21,22,23 . Estes fatores podem ocasionar redução na intensidade ou abolição do sinal sonoro no MAE.…”
Section: Discussionunclassified
“…Temporal bone studies have demonstrated that the condition of the middle ear in neonates is seldom pristine (Benner, 1940;Buch & Jorgensen, 1964;deSa, 1973deSa, , 1983Hemsath, 1936) with MEE present in up to 50% of ears (deSa, 1973;Eavey, 1993). The middle ear and antrum of a neonate have been reported to contain some amniotic fluid or residual mesenchyme and its cellular content.…”
Section: External/middle Ear Pathology and Conductive Hearing Loss Inmentioning
confidence: 99%
“…have pointed out that otitis media with effusion may contribute up to 67% of the false positive newborn hearing screens. Amniotic fluid contents aspirated into the middle ear have been reported to contribute to conductive hearing loss in neonates (deSa, 1977;Eavey, 1993;Northrop et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation